Adoption of circular economy innovations: The role of artificial intelligence - Dirk Czarnitzki; Robin Lepers; Maikel Pellens (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
The circular economy represents a systematic shift in production and consumption, aimed at extending the life cycle of products and materials while minimizing resource use and waste. Achieving the goals of the circular economy presents firms with the challenge of innovating new products, technologies, and business models, however. This paper explores the role of artificial intelligence as an enabler of circular economy innovations. Through an empirical analysis of the German Community Innovation Survey, we show that firms investing in artificial intelligence are more likely to introduce circular economy innovations than those that do not. Additionally, the results indicate that the use of artificial intelligence enhances firms' abilities to lower production externalities (for instance, reducing pollution) through these innovations. The findings of this paper underscore artificial intelligence's potential to accelerate the transition to the circular economy.
Keywords: Q55; O31; 330; Circular economy; Innovation; Artificial intelligence